Unlocking climate finance for Africa’s food systems transformation: Lessons from the Africa Food System Forum Masterclass - Jalango, Dorcas Anyango; Siagbe, Golli; Ouedraogo, Issa; Ogutu, Elizabeth (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
The Masterclass “Catalyzing Transformation: Unlocking the Potential of Climate Finance for Resilient Food Systems” was convened by the Alliance of Bioversity International and CIAT during the Africa Food Systems Forum (AFS). The session equipped participants with practical tools and guidelines such as the Climate-Smart Agriculture Investment Plans (CSAIPs) can support countries in making informed investment decisions that unlock financing for resilient food systems. Drawing on country experiences from Kenya, Ethiopia, Senegal, and Zambia, the Masterclass showcased how CSAIPs help prioritize high-impact areas for agri-food transformation, align investments with national climate goals, and strengthen public–private collaboration. Participants also discussed innovative financing mechanisms and leadership approaches that enhance access to climate finance at community and national levels. Lessons shared provided actionable insights for scaling similar approaches across West Africa, reinforcing the role of evidence-based planning and inclusive finance in advancing climate-resilient food systems across the continent.